Response of luminance meters used for radiodiagnostic applications. Issue 1 (March 2021) - Garcia, I; Navarro, M; Macêdo, E; Jesus, D; Leite, H
Abstract: The objective of this work was to study the responses of the different luminance meters for a range of applications, with the purpose of quality control in radiodiagnosis (170 a 3500 cd/m 2 with white light source). Materials and methods: Were evaluated the calibration factors of 48 luminance meters, distributed in 10 different models for the point of 1000 cd/m 2 in 5500K. Results: The sample mean values of Piranha - 657 light probe, Ray Safe - Xi and X2 and Unfors - Light-O-Meter P10 meters, presented greater accuracy (spectral sensitivity f1 < 3% and total error fges < 7, 5%, according to the classification of DIN 5032-7 standard) and the sample of Fluke/Nuclear of Associates - 07-621 presented a difference of 34.6% in relation to the reference value with statistical significance. Conclusion: This study showed that for 48 equipments studied, the mean values of the calibration factors of 6 of the 10 models evaluated (which represents 62.4% of the total number of the sample) are convergent to the corrected reference value and/or within the range of ± 4.5% of uncertainty.